Limited şirketlerde payın haczi - Gürlek, Gülsüm (My University, 2010)
zure of Share in Limited Liability Companies ABSTRACT In reality most preferred limited liablity companies are including both partnership company and capital companies characteristics at their structure. Limited Liability Companies are preferred to then other kind of companies and that is the reason of increasing the problems related with that companies. Seizure of share in limited liability companies is related with commercial law, execution and bankruptcy law areas which are in scope of private law. Seizure of share in limited liability companies is currently applicable under the principles of, execution and bankruptcy law. As there is no special defined legal provision concerning this subject, several problems occurs in practice.Through the revision in execution and bankruptcy law – rule number 94 – a new arrangement is made concerned with seizure of share in limited liability companies. Although seizure of share in limited liability companies is possible according to our law, this method is not commonly used in practice Why this method is not commonly used in practice is also answered in this thesis. We have also considered the rules of Turkish commercial law bill in this thesis and dealed with the differences according to the existing rules.
Keywords: Hukuk; Limited Şirketleri; Özel Hukuk